2018
DOI: 10.1007/s10278-018-0055-1
|View full text |Cite
|
Sign up to set email alerts
|

A General Framework for Monitoring Image Acquisition Workflow in the Radiology Environment: Timeliness for Acute Stroke CT Imaging

Abstract: Many facets of an image acquisition workflow leave a digital footprint, making workflow analysis amenable to an informatics-based solution. This paper describes a detailed framework for analyzing workflow and uses acute stroke response timeliness in CT as a practical demonstration. We review methods for accessing the digital footprints resulting from common technologist/device interactions. This overview lays a foundation for obtaining data for workflow analysis. We demonstrate the method by analyzing CT imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…16 Other studies have also demonstrated that standardizing and reducing variation in multistep work processes can lead to improved efficiency in patient care. [17][18][19] For example, Siegel et al 19 describe that at their institution, they estimate that automatic image display protocols have increased their radiologist's interpreting efficiency by 10% and saved them approximately 45 min/d. The clinical significance of the small decrease in ED LOS with this single intervention is unclear and may warrant further study, but if each trauma patient sees a decrease in LOS of 12 minutes and many trauma patients are seen in 24-hour period, these time savings become more substantial, particularly when combined with other incremental time saving interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Other studies have also demonstrated that standardizing and reducing variation in multistep work processes can lead to improved efficiency in patient care. [17][18][19] For example, Siegel et al 19 describe that at their institution, they estimate that automatic image display protocols have increased their radiologist's interpreting efficiency by 10% and saved them approximately 45 min/d. The clinical significance of the small decrease in ED LOS with this single intervention is unclear and may warrant further study, but if each trauma patient sees a decrease in LOS of 12 minutes and many trauma patients are seen in 24-hour period, these time savings become more substantial, particularly when combined with other incremental time saving interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In studies where the Lean methodology is applied to radiology, “waiting” for people, information, or equipment is a critical signal of inefficient system processes 16 . Other studies have also demonstrated that standardizing and reducing variation in multistep work processes can lead to improved efficiency in patient care 17–19 . For example, Siegel et al 19 describe that at their institution, they estimate that automatic image display protocols have increased their radiologist's interpreting efficiency by 10% and saved them approximately 45 min/d.…”
Section: Discussionmentioning
confidence: 99%